Vasa praevia: Should we routinely screen high-risk women for this rare but serious condition?. (May 2018) - McQueen, Victoria; Speed, Michelle; Rutter, Susan; Gray, Thomas
Vasa praevia is described as the unprotected fetal vessels traversing through the placental membranes over the cervical os, below the fetal presenting part and unprotected by placental tissue or the umbilical cord. It is often not detected antenatally and presents with painless bleeding and rapid fetal compromise after spontaneous or artificial rupture of the membranes, which causes trauma to these vessels. It is a rare condition affecting one in 2500 pregnancies and has a reported perinatal mortality rate of up to 60%. More than 80% of cases of vasa praevia have at least one risk factor for the condition and it has been shown that identification of vasa praevia antenatally results in fetal survival rates of up to 97%. Risk factors include placenta praevia, velamentous cord insertion, bi-lobed placenta, succenturiate lobe, assisted reproduction and multiple pregnancy. Screening for vasa praevia with transvaginal ultrasound has been shown to be sensitive and cost effective when used in a targeted population where risk factors are present. Here, we present the antenatal assessment and management of a case of vasa praevia detected during the routine 20-week anatomy scan of a healthy primigravida, which resulted in elective caesarean section delivery of a healthy baby at 36 weeks' gestation. The pathophysiology of vasa praevia is discussed and the methods and role of screening for this rare but serious condition are appraised.